88 names : a novel - Ruff, Matt (Harper, an imprint of HarperCollinsPublishers, 2020)
John Chu is a “sherpa" a paid guide to online role-playing games like the popular Call to Wizardry. For a fee, he and his crew will provide you with a top-flight character equipped with the best weapons and armor, and take you dragon-slaying in the Realms of Asgarth, hunting rogue starships in the Alpha Sector, or battling hordes of undead in the zombie apocalypse.